Distinct Immune Homeostasis Remodeling Patterns after HLA‐Matched and Haploidentical Transplantation - Huidong Guo; Liping Guo; Bixia Wang; Xinya Jiang; Zhigui Wu; Xiao‐Dong Mo; Yu‐Qian Sun; Yuan‐Yuan Zhang; Zhi‐Dong Wang; Jun Kong; Chen‐Hua Yan; Xiao‐Jun Huang (Advanced Science)
Abstract Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a widely used treatment for a variety of hematopoietic disorders, and also provides a valuable platform for investigating the development of donor‐derived immune cells in recipients post‐HSCT. The immune system remodels from the donor to the recipient during allo‐HSCT. However, little is known about the cell profile alterations as donor homeostasis rebalances to recipient homeostasis following HSCT. Here, multi‐omics technology is applied at both the single cell and bulk sample levels, as well as spectrum flow cytometry and fluorescent transgenic mouse models, to dissect the dynamics of the rebalanced homeostatic immune system in recipients after allo‐HSCT. The data reveal that all immune subpopulations observed in donors are successfully restored in recipients, though with varying levels of abundance. The remodeling of immune homeostasis exhibits different patterns in HLA‐matched and haploidentical HSCT, highlighting distinct biases in T cell reconstitution from the central and peripheral pathways. Furthermore, ZNF683 is critical for maintaining the persistence and quiescence of CD8 T‐cell in haploidentical HSCT. The research can serve as a foundation for developing novel strategies to induce immune tolerance.